Du Bestiaire dans le théâtre de W.B. Yeats - Pierre Longuenesse (Sillages Critiques, 2016)
Yeats’s drama is thoroughly filled with animals. Birds of all kinds, cats, donkeys, pigs and of course horses : a whole bestiary runs across all the plots and talk in his plays. In the beginning, the project of the Miracle Plays cycle determines this concrete and spiritual landscape, where diabolical creatures confront divine figures, and dissonant sounds contrast with birdsong. Later, in the Plays for Dancers, Yeats creates a different acoustic universe, mostly « acousmatic », in which animals are paradoxically the manifestations of the spiritual aspect of the natural world. Eventually, one of these animals is singled out: the « hawk-woman » of At the Hawk’s Well, for the creation of which Yeats and Michio Ito spent so much time in the London zoo. We must look back to Kleist and Craig to understand what is at stake with this « guardian of the well ». In fact, poet and dancer are fascinated by this particular bird because of the hawk’s power to surpass the hero, as the bear triumphs of the swordsman in Kleist’s On the marionnette theatre : in At the Hawk’s Well, the bird overcomes the man because it has a grace that the man will never find. Therefore, the « hawk-dancer » is this figure of original innocence, or the representation of the unity of being that Cuchulain seeks in vain.